2001
DOI: 10.1016/s1074-7613(01)00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound TNF Supports Secondary Lymphoid Organ Structure but Is Subservient to Secreted TNF in Driving Autoimmune Inflammation

Abstract: Mice without secreted TNF but with functional, normally regulated and expressed membrane-bound TNF (memTNF(Delta/Delta) mice) were created by knocking-in the uncleavable Delta 1-9,K11E TNF allele. In contrast to TNF-deficient mice (TNF(-/-)), memTNF supported many features of lymphoid organ structure, except generation of primary B cell follicles. Splenic chemokine expression was near normal. MemTNF-induced apoptosis was mediated through both TNF-R1 and TNF-R2. That memTNF is suboptimal for development of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
231
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(252 citation statements)
references
References 47 publications
19
231
1
1
Order By: Relevance
“…S1). These results confirm the requirement for soluble TNF in the lethality observed in the LPS/D-gal shock model [17,40].…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…S1). These results confirm the requirement for soluble TNF in the lethality observed in the LPS/D-gal shock model [17,40].…”
Section: Resultssupporting
confidence: 84%
“…S1). These results confirm the requirement for soluble TNF in the lethality observed in the LPS/D-gal shock model [17,40].Having established proper regulation of tmTNF D1-12 at both the transcriptional and the expression levels, we further addressed the issue of bioactivity by examining its ability to promote thymocyte proliferation. It has been shown that signaling through p75TNFR, but not p55TNFR, is essential to enhance the proliferation of mitogen-activated thymocytes [41].…”
supporting
confidence: 63%
See 2 more Smart Citations
“…[20][21][22] Th2-like expression profiles were induced by addition of hrIL4 and a-INFg to the cell culture and Th1-like conditions by tumor necrosis factora addition, respectively. [23][24][25][26][27] Cells without stimulation were used as control. IL4-stimulated Jurkat cells showed significantly different levels of luminescence for the tested constructs, with the T variation exceeding the intensity of the C allele (Statistical Product and Service Solutions (SPSS)-Tukey test, Po0.05) as well as the vector without insert (SPSS-Tukey test, Po0.002) (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%